The Diversity of Arbuscular Mycorrhizal Fungi in the Black Cumin Rhizosphere (Nigella sativa L.) in Cianjur, West Java, Indonesia - Al Asad, Faisal; Kurniawati, Ani; Budi R, Sri Wilarso; Faridah, Didah Nur (Department of Agronomy and Horticulture, IPB University, 2018)
Arbuscular Mycorrhizal Fungi (AMF) is a type of fungus that can form a symbiotic mutualism with most plants. Some AMF can only be symbiotic with a certain plant species. This research aims to determine and obtain the genus AMF from black cumin (Nigella sativa L.) accessions from America, Turkey, Hong Kong, Slovenia, India, and Kuwait accessions which had been grown in West Java, Indonesia. Three samples from each accession, four replications each, were collected for examination. The results showed that six generas of AMF were found in the rhizosphere of black cumin: Glomus, Gigaspora, Acaulospora, Scutellospora, Dentiscutata, and Entrophospora. The genus Glomus was predominantly found in the Indian accession, i.e. 96.42 spores.Keywords: black cumin, diversity, fungi, exploration, AMF